A staged reconstruction technique utilizing bioprosthetic mesh reinforcement in the repair of giant omphalocele - Annahita R. Fotouhi; Justin M. Sacks; Martin S. Keller; Kamlesh B. Patel (Elsevier, 2022)
Reconstruction of complex anterior abdominal wall defects, such as giant omphaloceles, remains a reconstructive challenge for plastic and pediatric surgeons. Though several repair techniques have been described in the literature, no standardized method has been explicitly developed to treat pediatric patients. The utilization of intraabdominal tissue expanders to augment the abdominal domain has been reported as a potential repair technique. Despite its documented application, substantial controversy remains regarding tissue expander implementation due to its associated complications. We describe a staged reconstruction technique with acellular dermal matrix-assisted musculofascial reconstruction followed by delayed skin closure. Utilization of this bioprosthetic mesh in the reconstruction of anterior abdominal wall defects is well-described in the adult population. We applied the principle to a preschool-aged child with a giant omphalocele. This technique provides a medium to bolster the musculofascia, limit the formation of visceral adhesions, decrease the need for numerous procedures, and reduce the risk of infection or pulmonary compromise. This report denotes that a bioprosthetic mesh reinforcement technique may be utilized for functional reconstruction of large, complex abdominal wall malformations in the pediatric population.